2017
DOI: 10.15171/jlms.2017.s6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of Low Level Laser therapy and Transcutaneous Electric Nerve Stimulation on Temporomandibular Joint Disorders

Abstract: IntroductionTemporomandibular joint disorder (TMD) is a general term for clinical problems in temporomandibular joints (TMJs), masticatory muscles, and surrounding tissues, which manifest as limitations in motion and joint sounds. 1 TMD is the second most-common skeletal-muscular problem and one of the most common chronic problems involving orofacial pain, discomfort and disability. Approximately 75% of the population has several symptoms of TMD and 33% have at least one symptom. 2-5The etiology of TMD, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0
14

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(125 citation statements)
references
References 34 publications
1
110
0
14
Order By: Relevance
“…The study by Kato.et al [10] and Sei .et al [12] revealed that both LLLT and TENS caused a noticeable decrease in painful symptoms for the short term, which may account for the cumulative effect. Nunez.et al [14] supported that LLLT was more e cient than TENS in improving the amplitude of mandibular movement.…”
Section: Summary Of Evidencementioning
confidence: 96%
See 4 more Smart Citations
“…The study by Kato.et al [10] and Sei .et al [12] revealed that both LLLT and TENS caused a noticeable decrease in painful symptoms for the short term, which may account for the cumulative effect. Nunez.et al [14] supported that LLLT was more e cient than TENS in improving the amplitude of mandibular movement.…”
Section: Summary Of Evidencementioning
confidence: 96%
“…Then 55 potentially eligible articles were obtained by screening the titles and abstracts carefully. After careful full-text screening and assessment of the risk of bias, 20 RCTs met the inclusion criteria [4,10,12,15,28,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. This selection process and exclusion reasons were presented in the ow chart (Fig.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations